Rethinking Universal Accessibility: A broader approach considering the digital gap - Abascal, Julio; Barbosa, Simone D. J.; Dearden, Andrew; Joshi, Anirudha; Ochieng, Daniel Orwa; Weber, Gerhard; Zaphiris, Panayiotis (My University, 2013)
Universal Accessibility aims at including all people with disabilities in the target population for user-centered design. It is usually focused on the needs of people with disabilities, frequently including elderly people. Current advancements in the Design for all concept may require complex equipment, advanced network environments, or computer training. Therefore, these products or services may fall out the access of many people with disabilities because economical, technological or formative restric-tions. This is a frequent situation in developing countries, but it is becoming common also in developed countries where poverty and emigration are frequently associated with barriers to access to assistive technologies and services. This Workshop aims at rethinking the concept of Universal Accessibility in order to find ways to include all excluded people with disabilities. It is organized on behalf of the IFIP WG 13.3 HCI and Disability for HCI for academics, designers, managers, etc., interested in creating methodologies, tools and products for a wider market, considering ethic and social requirements. Thus, the main objective of this workshop is to discuss the possibility of broadening the Universal Accessibility concept to include geopolitical and socio-economical circumstances. Experiences in fighting the Digital Gap will especially be welcome.
INTERACT 2013 Workshop on Rethinking Universal Accessibility: A broader approach considering the digital gap
Keywords: Universal accessibility; People with disabilities; Digital gap